Who pays for the cost of change? On the different antibiotic use patterns in three Nordic pig-meat settings - Waluszewski, Alexandra; Harrison, Debbie; Munksgaard Kristin B.; Halinen, Aino (Elsevier, 2026)
Animal-based food production accounts for two thirds of global antibiotic consumption (Van Boeckel et al.,
2017) yet reducing antibiotic use is key to sustainable agriculture (Kirchhelle, 2018; Helliwell et al., 2020). The
purpose of this empirical paper is to investigate the driving forces and hindrances behind the successful disembedding of the routine use of antibiotics in animal welfare practices in the Swedish, Norwegian and Danish pig meat settings. The Swedish and Norwegian settings represent Europe's lowest use of antibiotics for food animals and Antimicrobial Resistance (AMR) occurrence is rare. In Denmark, the use is below the EU average, but there is a high prevalence of AMR. Using the Industrial Network Approach (INA), our study shows how the current restricted use of antibiotics in the Nordic pig meat setting was the outcome of a mixture of voluntary and regulated change, and above all, the ability to distribute the costs of change. As such, multi-actor change towards more sustainable agriculture requires the ongoing collaboration between policy and business, along with significantpossibilities for farmers to share the costs of change.